2006
DOI: 10.1194/jlr.m600111-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between lipoproteins and bee venom phospholipase A2 in relation to their anti-plasmodium toxicity

Abstract: We previously showed that the in vitro intraerythrocytic development of the malarial agent Plasmodium falciparum is strongly inhibited by secreted phospholipases A 2 (sPLA 2 s) from animal venoms. Inhibition is dependent on enzymatic activity and requires the presence of serum lipoproteins in the parasite culture medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…LA considerably inhibited the growth of P. falciparum in vitro, as well as of Plasmodium vinckei petteri and Plasmodium yoelii nigeriensis in mice; however, antioxidant compounds markedly decreased the fatty acid‐induced parasite killing effect (Krugliak et al, ; Kumaratilake, Robinson, Ferrante, & Poulos, ). Hence, LA may be expected to exert toxicity to cultured P. falciparum via extracellular production of linoleate peroxides/epoxides (Guillaume, Calzada, Lagarde, Schrevel, & Deregnaucourt, ). Additionally, antiplasmodium potential of phenolics and flavonoids in GSO would have to be addressed via malaria parasite metabolism and development (Alson et al, ; Cai, Zhang, Ji, & Xing, ; Kusch et al, ; Palaniswamy, Pradeep, Sathya, & Angayarkanni, ).…”
Section: Discussionmentioning
confidence: 99%
“…LA considerably inhibited the growth of P. falciparum in vitro, as well as of Plasmodium vinckei petteri and Plasmodium yoelii nigeriensis in mice; however, antioxidant compounds markedly decreased the fatty acid‐induced parasite killing effect (Krugliak et al, ; Kumaratilake, Robinson, Ferrante, & Poulos, ). Hence, LA may be expected to exert toxicity to cultured P. falciparum via extracellular production of linoleate peroxides/epoxides (Guillaume, Calzada, Lagarde, Schrevel, & Deregnaucourt, ). Additionally, antiplasmodium potential of phenolics and flavonoids in GSO would have to be addressed via malaria parasite metabolism and development (Alson et al, ; Cai, Zhang, Ji, & Xing, ; Kusch et al, ; Palaniswamy, Pradeep, Sathya, & Angayarkanni, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of phospholipase A 2 towards Plasmodium development has been extensively studied (Deregnaucourt & Scrével, 2000; Zieler et al ., 2001; Guillaume et al ., 2004), although the exact mechanism of action is not completely understood. In culture, PLA 2 s have an indirect effect by degrading lipoproteins present in serum, which in turn produce components (eg arachidonic, linoleic and docosahexaenoic acid) toxic to the parasite (Guillaume et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that venom sPLA 2 s exert an indirect killing of P. falciparum through hydrolysis of human plasma phospholipids (PLs) present in the parasite culture medium (3,4). We also demonstrated that the enzymatic hydrolysis of human lipoproteins by bee venom sPLA 2 generates lipid products that are toxic to the parasite (6). Nonesterified fatty acids (NEFAs), especially polyunsaturated NEFAs (PUFAs), were identified as the main mediators of parasite death.…”
mentioning
confidence: 98%